Importancia del manejo agronómico del cultivo de ajonjolí (Sesamum indicum L.) en Ecuador - Bajaña Morán, Darwin Andrés (2022)
This document dealt with the agronomic management of sesame (S. indicum L.) cultivation in Ecuador, where it is concluded that there is little information regarding scientific research that generates good agronomic management of the crop and increases yields; sesame is an annual plant, autogamous with oily seeds, also known as sesame, whose cycle can vary between 80 and 130 days. The plant contains between 50 and 60% oils which are highly stable, 25% proteins, 11% carbohydrates, 4% fibers, 5% ash, 5% moisture and natural antioxidants such as sesamolin, sesamin and sesamol The composition of its oils varies according to the varieties; The crop is planted at 75 cm between furrows and 5 to 10 cm between plants and in branched varieties at 90 cm between furrows and 10 or more cm between plants, with which a population range of 150,000 to 200,000 plants/ ha and among the benefits of the sesame plant is that they are ornamental in gardens, medicinal plant, bakery industry, sweets and in the preparation of food and refreshing beverages. In Latin America these drinks are a traditional element of the diet of nursing women, because they stimulate milk production.